Shale gas transport behavior considering dynamic changes in effective flow channels. Issue 5 (31st July 2019) - Chen, Mingjun; Kang, Yili; Zhang, Tingshan; Li, Xiangchen; Lin, Chong
Abstract: Shale gas transport is influenced by the changes in effective flow channels during production due to an effective stress sensitivity and a sorption layer effect. In this work, shale samples' core analyses, methane adsorption experiments, and effective stress sensitivity experiments were conducted at in situ conditions. Then, a mathematical modeling was applied to quantitatively determine the real shale gas flow behavior considering the changes in effective flow channels during production. The results show that (1) the gas transport capability in matrix has an obvious tendency of increase in the mid‐late production period; (2) the decline of permeability of inorganic pores/fractures tends to be gentler during production, especially for the smaller flow channels; (3) surface diffusion is dominant in shale matrix throughout production; (4) the contribution of Knudsen diffusion to total gas flux cannot be neglected in flow channels with hydraulic radius of tens of nanometers in the early production period or of tens and hundreds of nanometers in the mid‐late production period; and (5) viscous flow generally dominates the total gas flux in flow channels with hydraulic radius more than 10 nm in the early production period or more than 100 nm in the mid‐late production period. This work is beneficial for an accurate evaluation of shale gas transport during production. Abstract : Shale gas transport is influenced by the changes in effective flow channels during production due to an effective stress sensitivity and a sorption layer effect. In this work, shale samples' core analyses, methane adsorption experiments, and effective stress sensitivity experiments were conducted at in situ conditions, and a unified model was constructed to describe the real shale gas flow behavior during production.